Development and characterization of monoclonal antibodies against the extracellular domain of African swine fever virus structural protein, CD2v - Liu, Siyuan; Ding, Peiyang; Du, Yongkun; Ren, Dongna; Chen, Yilan; Li, Minghui; Sun, Xueke; Wang, Siqiao; Chang, Zejie; Li, Ruiqi; Zhang, Gaiping (Frontiers in Microbiology, 2022)
African swine fever virus (ASFV), a DNA double-stranded virus with high infectivity and mortality, causing a devastating blow to the pig industry and the world economy. The CD2v protein is an essential immunoprotective protein of ASFV. In this study, we expressed the extracellular region of the CD2v protein in the 293F expression system to achieve proper glycosylation. Monoclonal antibodies (mAbs) were prepared by immunizing mice with the recombinant CD2v protein. Eventually, four mAbs that target the extracellular region of the ASFV CD2v protein were obtained. All four mAbs responded well to the ASFV HLJ/18 strain and recognized the same linear epitope, 154SILE157. The specific shortest amino acid sequence of this epitope has been accurately identified for the first time. Meaningfully, the 154SILE157 epitope was highly conformed in the ASFV Chinese epidemic strain and Georgia2008/1 strains according to the analysis of the conservation. These findings contribute to further understanding of the protein function of CD2v and provide potential support for the development of diagnostic tools and vaccines for ASFV.